ANALISIS DETERMINAN TERHADAP MANAJEMEN KEUANGAN MAHASISWA PROGRAM STUDI AKUNTANSI DI PERGURUAN TINGGI SWASTA KOTA DENPASAR - Ernawatiningsih, Ni Putu Lisa (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
This study aims to examine the influence of financial knowledge and love of money on the financial management of students at private universities in Denpasar City. The population in this study is all students of accounting undergraduate program with the criteria of sampling using purposive sampling method. The data used in this study are primary data collected through questionnaire survey and data analysis techniques using multiple regression analysis. The results obtained show that financial knowledge and love of money have a positive effect on financial management of accountancy student study program at private universities in Denpasar City.